Does Income Matter? Moderating Effect on Financial Literacy and Financial Behavior - Sunarmi Sunarmi; Vivi Hapsari; Syiriac Nellikunnel Devashia (Yayasan Darussalam Bengkulu, 2026)
Background: Financial management behavior is essential for individual well-being, particularly among private school teachers in Indonesia with fixed incomes who still face financial challenges. This study is based on the Theory of Planned Behavior, which explains behavior through cognitive, social, and psychological factors. Financial literacy, financial socialization, and self-control are proposed as key determinants, while income is examined as a moderating variable to capture the role of economic capacity. Method: Participants in this study were private teachers with fixed incomes in Indonesia. A total of 150 valid questionnaires were collected and analyzed using a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) using Smart PLS. Results: These findings indicate that the effectiveness of financial knowledge, social environmental influences, and self-control in shaping financial behavior is highly dependent on an individual's economic capacity. Conclusion: This study has two main implications. First, the results provide important insights for educational institutions and policymakers in designing programs to improve financial literacy and well-being, particularly for educators. These two studies contribute to the development of the financial behavior literature by expanding the application of the Theory of Planned Behavior through the integration of the moderating variable of income as a contextual factor in explaining individual financial management behavior.